Step into ancient Japan - Macdonald, Fiona (London Lorenz Books, 1999)
Contains fifteen step-by-step projects designed to help children learn about ancient Japanese civilizations.
Includes index
Keywords: Japan -- History -- Juvenile literature; Japan -- Social life and customs -- To 794